STRATEGI MENINGKATKAN LOYALITAS DAN KINERJA KARYAWAN (STUDI PADA AYEE CAFE, MOJOROTO, KEDIRI) - Sri Hariyanti; Diyan Rizqianto (Istithmar: Jurnal Studi Ekonomi Syariah, 2021)
The role of human resources (HR) in a company is very significant and has enormous potential to carry out company activities. Therefore, humans function as the main driving force in every activity carried out by the company. Therefore, human resources should be empowered as much as possible in order to be able to produce optimal output. Good HR management will also affect the increase in company productivity and profitability. And one way that can be taken is by increasing the loyalty and performance of employees to develop companies. This study uses a qualitative method by taking place at Ayee Cafe, Mojoroto-Kediri. The purpose of this study was to determine the operational management Ayee Cafe and how the strategy is to increase employee loyalty and performance. Ayee cafe has a special way to increase employee loyalty and performance that has been implemented for the last 5 years. Ayee cafe also considers all those involved in helping its business as employees. It's just that the owner's job is to manage the business, if the boss makes himself the owner, there will be no discipline. Because what comes to mind is that the owner's name is only receiving the results, that's what the owner of Ayee Cafe avoids.